On the k-Jacobsthal numbers by matrix methods - Srisawat, Somnuk; Sriprad, Wanna; Sthityanak, Oam (Progress in Applied Science and Technology, 2015)
In this paper, we define the Jacobsthal matrix and Jacobsthal matrix. After, by using this matrix representation, we obtain some identities and the Binet’s formula for Jacobsthal numbers.